Meta-analytic effect of Saccharomyces cerevisiae on dry matter intake, milk yield and components of lactating goats - Ogbuewu, Ifeanyi Princewill; Mbajiorgu, Christian Anayo (Frontiers in Veterinary Science, 2022)
The results of investigations on the impact of Saccharomyces cerevisiae (SC) on performance characteristics of lactating goats are inconsistent. Thus, this study aimed to summarize available evidence on the effect of SC supplementation on dry matter intake (DMI), milk yield and composition in lactating goats using meta-analysis. A systematic search performed on Scopus, Google Scholar and PubMed databases yielded 1,368 studies of which 18 were used for the meta-analysis. Subgroup and meta-regression analyses were performed to explore the sources of heterogeneity in response to dietary SC supplementation. A random-effects model showed that SC had a moderate effect on milk yield [standardized mean differences (SMD) = 0.51; 95% CI: 0.20 to 0.82, p = 0.001] and milk fat (SMD = 0.30; 95% CI: 0.05 to 0.55, p = 0.02) in lactating goats when compared to the controls. Subgroup analysis by SC type indicated that live SC had a large to moderate effect on milk yield (SMD = 1.46; 95% CI: 0.96 to 1.96, p < 0.001) and milk fat (SMD = 0.51; 95% CI: 0.19 to 0.84, p = 0.002), whereas dead SC had a large negative effect on DMI (SMD = −0.82; 95% CI: −1.28 to −0.7, p < 0.001) and a moderate reduction effect on milk yield (SMD = −0.55; 95% CI: −0.99 to −1.96, p = 0.015). We found significant heterogeneity across studies that evaluated the effect of SC treatment on DMI and milk yield in lactating goats and meta-regression analysis explained most of the sources of heterogeneity. In conclusion, pooled results showed that dietary SC supplementation increased milk yield and fat in lactating goats. In addition, subgroup analysis revealed that both live and fermented SC increased milk yield and fat in lactating goats, while dead SC reduced DMI and milk yield.